Medical genetics : its application to speech, hearing, and craniofacial disorders - Robin, Nathaniel (Genetic syndromes and communication disorders series., 2008)
This book reviews the rapidly developing field medical genetics from theories to its implications for clinical practice. This book covers the whole field of medical genetics from a general overview of the profession to details of effective treatment of patients with common and esoteric genetic disorders--including birth defects, hearing loss, oro-facial clefting, craiosynostosis, and much more. Crucially, as issues surrounding breakthroughs in understanding and development of new technologies in genetics have risen to the fore of the cultural consciousness, it gives coverage to the many ethical questions raised.